A Learner Centered Approach of Teaching and Learning in Pharmacology: A Questionnaire Based Analysis of Student Cognizance and Experiences - Rao, Rashmi Raghava; Shenoy, Preethi Jnaneshwara; Ullal, Sheetal Dinakar; Kamath, Ashwin (Indian Journal of Pharmaceutical Education and Research, 2020)
Background: Innovative and flexible educational methods like Problem Based Learning (PBL) and integrated teaching practices were integrated into the Pharmacology course in a manner that they complement the didactic lectures or, completely replace the lecture classes with the aim to optimize the educational atmosphere for a better learner experience. Aim: The present study is an attempt to gather feedback on newer teaching learning methods and audiovisual aids employed during the didactic lectures and small group teaching sessions newly introduced into the curriculum. Methods: The study is a cross sectional questionnaire-based analysis. The questionnaires were distributed to the second-year medical students inviting them to share their opinion on usefulness of current teaching-learning methods. The data collected was analyzed by means of descriptive statistics. Results: The students rated small group discussions and small testsassessment for learning to be more useful in understanding the subject as well as scoring more marks in the examinations (Likert score of 4.5 and 4.51 respectively). Didactic lectures were less useful with a Likert score of 3.71. Both problems based learning and integrated teaching scores were equivocal with more students favoring integrated teaching. Conclusion: Student feedback forms the backbone for continuing revisions of undergraduate curriculum with the aim of making the subject more learner-oriented and practically relevant. Constant review of our current methodology will reflect on success of newer teaching-learning methods introduced in encouraging learning. It would enable us to incorporate appropriate changes in curricula where and when necessary.
Keywords: Teaching learning methods; PBL; Integrated teaching; Student perception; Audiovisual aids; Active learning